The Mediterranean Diet is Not Related to Cognitive Change in a Large Prospective Investigation: The PATH Through Life Study - Cherbuin, Nicolas; Anstey, Kaarin J. (The American journal of geriatric psychiatry, 2012)
To determine whether the Mediterranean diet and other dietary variables are predictors of transition from healthy cognitive aging to mild cognitive impairment and cognitive decline. Longitudinal. We assessed 1528 individuals, aged 60–64 years, who were participating in a prospective epidemiological study of mental health and aging. We tested participants at two time points, 4 years apart, for mild cognitive impairment using either the International Consensus Criteria, impairment on the Clinical Dementia Rating scale (Clinical Dementia Rating: 0.5), or any of a suite of criteria sets (any mild cognitive disorder). We used logistic regression to assess the dietary predictors of conversion to clinical diagnoses and multiple regression to identify the predictors of cognitive decline (change in global cognition) in healthy participants. Of the 1528 participants with no cognitive impairment in the first wave of assessment and complete data, 10 participants were diagnosed with mild cognitive impairment, 19 with Clinical Dementia Rating 0.5, and 37 participants presented with any mild cognitive disorder at follow-up. Adherence to Mediterranean diet was not found to be protective against cognitive decline but excessive caloric intake, and high intake of monounsaturated fats was predictive of mild cognitive impairment. In this large longitudinal investigation of generally healthy individuals Mediterranean diet was not found to be protective of cognitive decline.